2019
DOI: 10.3389/fimmu.2019.01579
|View full text |Cite
|
Sign up to set email alerts
|

Three Novel Players: PTK2B, SYK, and TNFRSF21 Were Identified to Be Involved in the Regulation of Bovine Mastitis Susceptibility via GWAS and Post-transcriptional Analysis

Abstract: Bovine mastitis is a common inflammatory disease caused by multiple factors in early lactation or dry period. Genome wide association studies (GWAS) can provide a convenient and effective strategy for understanding the biological basis of mastitis and better prevention. 2b-RADseq is a high-throughput sequencing technique that offers a powerful method for genome-wide genetic marker development and genotyping. In this study, single nucleotide polymorphisms (SNPs) of the immune-regulated gene correlative with mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 107 publications
(111 reference statements)
0
13
0
1
Order By: Relevance
“…Interestingly, SLC38A1 was abundantly expressed in the Yunling cattle's pituitary glands, and SLC38A3 was abundantly expressed in the Leiqiong cattle's pituitary glands. In our previous study, we also found that SLC38A4 was abundantly expressed in the Simmental cattle pituitary gland compared with Wenshan cattle [56]. There are many reports to prove that SLC38A1, SLC38A3, and SLC38A4 are involved in mammalian growth regulation, and SLC38A1 and SLC38A4 are primarily implicated in growth control of the embryo and can positively regulate prenatal growth by regulating the release of insulin [57].…”
Section: Discussionmentioning
confidence: 75%
“…Interestingly, SLC38A1 was abundantly expressed in the Yunling cattle's pituitary glands, and SLC38A3 was abundantly expressed in the Leiqiong cattle's pituitary glands. In our previous study, we also found that SLC38A4 was abundantly expressed in the Simmental cattle pituitary gland compared with Wenshan cattle [56]. There are many reports to prove that SLC38A1, SLC38A3, and SLC38A4 are involved in mammalian growth regulation, and SLC38A1 and SLC38A4 are primarily implicated in growth control of the embryo and can positively regulate prenatal growth by regulating the release of insulin [57].…”
Section: Discussionmentioning
confidence: 75%
“…A recent study, in which a genotyping-by-sequencing approach was used to find novel SNPs associated with milk traits, showed that the majority of identified SNPs were located within intergenic regions (69%), followed by intronic regions (25%), with only 3.46% of SNPs being coding variants [ 44 ]. Moreover, different studies found that conserved non-coding regions in introns and near genes show large allelic frequency shifts, similar in magnitude to missense variations, suggesting that they are critical for gene function regulation and evolution in many species [ 45 , 46 ]. Most of the significant SNPs detected in our investigation are located inside or in proximity to complete or partial lncRNA-like or miRNA-like sequences, or to repeated regions containing SINEs or LINEs, and it is now established that both intronic and LINE/SINEs repeats could lead to transcriptional regulation of the affected genes [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the pathogenic molecular mechanism of mastitis caused by S. agalactiae, the experts' views are highly variable, and no conclusions have been reached. Our previous research found that TNSFRSF21 genetic polymorphisms are signi cantly related to the susceptibility and tolerance of dairy cow mastitis through a genome-wide association analysis [31]; however, the role of TNFRSF21 in S. agalactiae-induced mastitis remains unknown. In this study, we found that the mammary gland tissues of the mice infected with S. agalactiae (bacterial solution with a concentration of 1 × 10 9 CFU/mL) displayed more severe histopathological damage than that of the control groups, and the level of caspase-1, IL-1β, NLRP3, and TNFRSF21 expression was signi cantly increased.…”
Section: Discussionmentioning
confidence: 99%